2021
DOI: 10.14482/sun.36.1.616.2
|View full text |Cite
|
Sign up to set email alerts
|

Perception of discrimination in a group of colombian general practitioners during the COVID-19 pandemic and its relation to labor and psychological factors

Abstract: Objetivo: estimar la prevalencia de percepción de discriminación y su asociación con estrés laboral, ansiedad y miedo al COVID-19 en médicos generales colombianos. Métodos: Estudio transversal que pertenece al proyecto Dinámicas Psicosociales Universitarias, aval institucional de la Universidad de Cartagena, Colombia. Médicos generales colombianos fueron invitados por redes sociales a diligenciar, los primeros cinco días de abril-2020, un formulario Google Forms© con preguntas sobre temores y opiniones respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…However, the results should be contextualized, because a little over 80% of the sample in this study were women, with professions linked to gender (nurses and nursing assistants). Moreover, our findings are supported by studies by [ 2 , 3 , 6 , 11 , 15 , 33 , 39 , 40 , 42 , 45 , 52 , 62 , 63 , 64 , 68 , 86 ], as they show that being a woman is decisive in exhibiting high anxiety about the consequences of COVID-19, regardless of the country of origin of the study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, the results should be contextualized, because a little over 80% of the sample in this study were women, with professions linked to gender (nurses and nursing assistants). Moreover, our findings are supported by studies by [ 2 , 3 , 6 , 11 , 15 , 33 , 39 , 40 , 42 , 45 , 52 , 62 , 63 , 64 , 68 , 86 ], as they show that being a woman is decisive in exhibiting high anxiety about the consequences of COVID-19, regardless of the country of origin of the study.…”
Section: Discussionsupporting
confidence: 89%
“…Our results show that there are no significant differences between the anxiety levels of health personnel depending on whether they provided care for patients with COVID-19. These results differ from those of [ 11 , 67 ], and other authors who showed that there were mental health problems, such as anxiety, depression, post-traumatic stress in the healthcare population, mainly in people working in the front line with COVID-19 patients, which may be due to the fear of contagion, work stress, and witnessing coworkers die [ 1 , 5 , 6 , 7 , 8 , 18 , 19 , 22 , 23 , 26 , 39 , 40 , 41 , 42 , 44 , 45 , 52 , 53 , 57 , 58 , 59 , 61 , 62 , 63 , 65 , 69 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations